2018
DOI: 10.5269/bspm.v36i3.33081
|View full text |Cite
|
Sign up to set email alerts
|

Existence of solutions for an elliptic p(x)-Kirchhoff-type systems in unbounded domain

Abstract: In this paper we study of the existence of solutions for a class of elliptic system with nonlocal term in R N . The main tool used is the variational method, more precisely, the Mountain Pass Theorem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Problems which involve the p(. )-Kirchhoff type have been intensively studied in the recent years, because of their numerous and relevant applications in many fields of mathematics, for example, electrorheological fluids (see [2]), elastic mechanics ( [1]), image restoration ( [7]). For this type of operator combined with a system of Kirchhoff functions we recall [1,5,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems which involve the p(. )-Kirchhoff type have been intensively studied in the recent years, because of their numerous and relevant applications in many fields of mathematics, for example, electrorheological fluids (see [2]), elastic mechanics ( [1]), image restoration ( [7]). For this type of operator combined with a system of Kirchhoff functions we recall [1,5,11].…”
Section: Introductionmentioning
confidence: 99%
“…)-Kirchhoff type have been intensively studied in the recent years, because of their numerous and relevant applications in many fields of mathematics, for example, electrorheological fluids (see [2]), elastic mechanics ( [1]), image restoration ( [7]). For this type of operator combined with a system of Kirchhoff functions we recall [1,5,11]. Inspired by the above articles, we aim in this paper to prove, under minoration conditions on A i=1,2 and periodic conditions on F , the existence of solutions for the system (1) by applying variational method and Ekeland's principle.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, by using the mountain pass theorem, the authors in [24] showed the existence of nontrivial solutions for system (1)…”
Section: Introductionmentioning
confidence: 99%